THE INPUT AGRICULTURAL INITIATION IN IMPROVEMENT RURAL WOMAN REALITY IN PROVINCES BABYLON AND HOLY KARBALA - & Eskander, Al-Taiy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The aim of this research is to identify agricultural loans reality of rural woman in the field Agricultural Initiation in Babylon, Holy Karbala for the period 2010- 2014 and level Benefit from it; and to determine problems of rural woman Borrowers. Data were collected from 100 rural woman Borrowers was about 14.3 from 700 rural woman during 25- 2-2015 unite l0- 4-2015 through questionnaire and interview. The four dimensional standard has been used to measure the degree of Benefit from it of rural woman from Agricultural Initiation, That included 22articlesd distributed on5 axes. The results showed that Averages of agricultural loans in 2010- 2014 is 4.85 M.ID /year. The results also showed weighted arithmetic mean for problems of rural woman (1.36-4) degree on weight percentile (34-100)%. and Satisfaction level of Benefit from agricultural loans is A small group The research recommends Activating the Monitoring and evaluation System of Program Agricultural Initiation.